Nutritional Formula Selection in Pediatric High-Output Stoma with Acute Kidney Injury: A Review Article - Gisheila Ruth Anggitha; Ariani Dewi Widodo; Adrian Himawan Singgih (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: High-output stoma (HOS) is a common complication in pediatric patients with ileostomy, often leading to dehydration, electrolyte imbalance, and malnutrition. These complications increase the risk of acute kidney injury (AKI), which is associated with high morbidity and mortality. Nutritional management in children with HOS and AKI is challenging, requiring careful formula selection to maintain adequate energy and protein intake, fluid and electrolyte balance, and optimize gastrointestinal tolerance. Discussion: In children with HOS and AKI, the selection of an appropriate enteral formula represents a critical component of nutritional management, aiming to mitigate dehydration, electrolyte disturbances, and protein-energy malnutrition. Isotonic or mildly hypotonic solutions are preferred to minimize osmotic losses. Electrolyte composition must be adjusted to account for impaired renal handling in AKI. Semi-elemental formulas are generally recommended as first-line therapy due to their enhanced absorptive properties and relatively lower potassium and phosphate content compared with polymeric preparations. Transition to polymeric formulas may be considered once stoma output stabilizes and renal function improves. Elemental formulas are reserved for severe malabsorption, intolerance, or when strict electrolyte restriction is required. Continuous enteral infusion is preferred during the acute phase to reduce stoma output volume and nutrient loss, with a gradual transition to intermittent bolus feeding to promote intestinal adaptation and stimulate gut hormone. Conclusion: Individualized nutritional management is essential in pediatric patients with HOS and AKI. Semi-elemental formulas, electrolyte adjustments based on renal function, and tailored feeding strategies help maintain fluid–electrolyte balance, prevent malnutrition, and support recovery and growth.